Exploration on Rubber Fortification In Concrete - Denesh, K. C.; Naveenraj, V.; Gowtham, S. K. (International Journal of Scientific Research in Civil Engineering, 2016)
Throughout the world, the disposal of used tires is a major environmental problem causing environmental hazards such as breeding ground for mosquitoes, producing uncontrolled fire and they are contaminating the soil and vegetation. Therefore, there is an urgent need to identify alternative outlets for these tyres, with the emphasis on recycling the waste tyre. Now, the use of waste tires in concrete has become technically feasible and the concrete is being considered as lightweight concrete. This study reviews the feasibility of using waste tires in the form of chips and fibers with different sizes in concrete to improve the strength as well as protecting the environment. The purpose of this research is based on the investigation of the use of fibers in structural concrete to enhance the mechanical properties of concrete. The objective of the study was to determine and compare the differences in properties of concrete containing without fibers and concrete with fibers. The different ratio of the fiber was carried out like 0.5%, 1.0%, 1.5%, 2.0% in the grade of M30 and M40 grade of concrete was used in this investigation. In this experimental investigation compressive strength, tensile strength and flexural strength tests was carried out at the age of 7, 28 days. Compare the results of conventional and fiber reinforced concrete (FRC).